Sonogashira cross-coupling over Au(1 1 1): from UHV to ambient pressure. (12th October 2017) - Johansson, N; Sisodiya, S; Shayesteh, P; Chaudhary, S; Andersen, J N; Knudsen, J; Wendt, O F; Schnadt, J
Abstract: We have studied the reaction of phenylacetylene (PA) with chloro-, bromo-, and iodobenzene on the Au(1 1 1) surface as a model system for the gold-catalysed Sonogashira cross-coupling. Both ultrahigh vacuum-based and ambient pressure x-ray photoelectron spectroscopy show that iodo- and chlorobenzene (IB and CB) undergo the cross-coupling reaction towards diphenylacetylene. Bromobenzene (BB), in contrast, does not react in the UHV experiments. Further, at ambient pressure signs are found for poisoning of the Au(1 1 1) surface by a carbon species formed in the reaction. The understanding obtained in the reaction experiments are based on a thorough investigation of the adsorption of PA, IB, CB, and BB on the Au(1 1 1) surface by soft x-ray absorption spectroscopy and temperature-dependent x-ray photoelectron spectroscopy. In particular, the experiments provide the orientation of the intact adsorbates with respect to the surfaces at liquid nitrogen temperature. Dissociation in the temperature regime between  −80 and  −15 °C is observed for iodo- and chlorobenzene, but not for BB, in agreement with that only IB and CB, but not BB, react with PA to form diphenylacetylene. The difference is tentatively attributed to a difference in surface orientation of the different halobenzenes.